Analysis of monitored cases of acquired syphilis in Porto Alegre, Rio Grande do Sul - Lermen, Gustavo Haas; Oliveira, Juanita Natasha Garcia de; Acosta, Lisiane Morelia Weide; Santos, Fabiana Ferreira dos (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: Syphilis is a systemic and curable sexually transmitted infection, exclusive to humans. Brazil is experiencing an increasing incidence of syphilis in recent years. Porto Alegre has an incidence rate of acquired syphilis (AS) four times higher than the national one. Objective: To describe the epidemiological profile of monitored cases of AS, through rapid tests, in the city of Porto Alegre/Rio Grande do Sul in the first semester of 2018. Methods: The study has a cross-sectional, observational, epidemiological, and analytical design, and the study population was included in the Porto Alegre AS monitoring spreadsheet in the first semester of 2018, totaling 1,453 participants. We performed descriptive analyses with absolute and relative frequencies to develop the profile. The χ2 test for bivariate analysis verified the association between sociodemographic variables and the adequate treatment outcome, with a 95% significance level. Results: The profile found had a predominance of males, white people, individuals aged 20 to 29, with incomplete elementary school, and not homeless. We identified an association in the bivariate analysis between the adequate treatment outcome and the variables schooling, gender, age, and homelessness. Conclusion: Actions that seek to structure and organize the processes related to AS monitoring are important, especially due to the association of sociodemographic variables that indicate social vulnerability with the adequate treatment outcome.